Unveiling the Controversy: Legal Analysis of Juvenile Narcotics Use for Medical Purposes - Abdurrakhman Alhakim; Emiliya Febriyani; Ampuan Situmeang; David Tan (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Purpose of the study: This research aimed to fill gap by detailing the arguments around legal responsibility of juvenile narcotics use that are not intended for recreational purposes, but rather for medical purposes. This seeks to contribute to the growing literature on restorative justice in Indonesia, particularly for the development of the juvenile justice system. Methodology: This study examined the phenomenon of narcotics uses in the self-medication context, particularly among youth, utilizing the normative legal research method and bolstered by a case study (Judicial Decision). It also utilized the statutory approach, which involved an in-depth analysis of applicable legal provisions regarding juvenile crimes and narcotics. Results: While conceptual analysis found that there are many connections between the emerging trend of self-diagnosis and self-medication with narcotics use among children, yet the normative support to deal with this phenomenon through restorative justice remains poor. The impact of the lack of normative support is shown in the judicial decision, in which restorative justice through the application of diversion was applied incautiously, blurring children’s well-being; disturbed by medical issue at first and later worsened by marijuana addiction. Applications of this study: The study can be an instrumental reference in guiding legal reforms, shaping healthcare policies for juvenile narcotic use, and providing information on educational and awareness programs that distinguish between medical and non-medical use of narcotics by minors. Novelty/Originality of this study: The originality of this study lies in its specific accent on the intersection of juvenile law, narcotics use, and medical treatment, which is a relatively underexplored area in legal research in Indonesia. It is also found in its analysis of a decision of a juvenile court regarding the use and possession of narcotics. Keywords: Legal Responsibility, Medical Purposes, Narcotics Crime, Restorative Justice, Case Study ABSTRAK Tujuan: Penelitian ini bertujuan untuk mengisi kesenjangan dengan menjelaskan argumen seputar tanggung jawab hukum penggunaan narkotika oleh anak di bawah umur yang tidak dimaksudkan untuk tujuan rekreasi, melainkan untuk tujuan medis. Penelitian ini juga dilakukan untuk berkontribusi terhadap berkembangnya literatur mengenai keadilan restoratif di Indonesia, khususnya untuk pengembangan sistem peradilan anak. Metodologi: Studi ini mengkaji fenomena penggunaan narkotika dalam konteks swamedikasi, terutama di kalangan anak-anak, dengan menggunakan metode penelitian hukum normatif yang didukung oleh studi kasus (Putusan Pengadilan). Studi ini juga menggunakan pendekatan undang-undang, yang melibatkan analisis mendalam terhadap ketentuan hukum yang ada mengenai tindak pidana remaja dan narkotika. Temuan: Analisis konseptual menunjukkan bahwa meskipun terdapat banyak keterkaitan antara tren berkembangnya swadiagnosis dan swamedikasi dengan penggunaan narkotika di kalangan anak-anak, dukungan normatif untuk mengatasi fenomena ini melalui keadilan restoratif masih kurang. Dampak dari kurangnya dukungan normatif ini terlihat dalam putusan pengadilan di mana keadilan restoratif melalui penerapan diversi diterapkan dengan tergesa-gesa, tanpa fokus pada kesejahteraan anak, yang awalnya terganggu oleh masalah medisnya dan kemudian memburuk akibat kecanduan ganja. Kegunaan: Studi ini dapat menjadi referensi penting dalam reformasi hukum, membentuk kebijakan kesehatan yang berkaitan dengan penggunaan narkotika pada anak, dan menginformasikan program pendidikan dan kesadaran yang membedakan antara penggunaan narkotika untuk tujuan medis dan non-medis oleh anak di bawah umur. Kebaruan/Orisinalitas: Orisinalitas penelitian ini terletak pada fokus spesifiknya pada titik temu antara hukum peradilan anak, penggunaan narkotika, dan perawatan medis, yang merupakan area yang kurang dieksplorasi dalam penelitian IndonesiaIndonesia. Orisinalitas juga terletak pada analisisnya terhadap putusan pengadilan anak mengenai penggunaan dan kepemilikan narkotika. Kata Kunci: Tanggung Jawab Hukum, Tujuan Medis, Kejahatan Narkotika, Keadilan Restoratif, Studi Kasus